Penerapan Model Scaffolded Reading untuk Meningkatkan Pemahaman Membaca Siswa - Syarifah, Novi; Wahyudin, Wahyudin; Nurteti, Lilis (Jurnal Penelitian Pendidikan Islam, 2016)
This study aims to improve students' reading comprehension in SDN 2 Kawalimukti Ciamis. The method used is the classroom action research. Data were collected through observation and test performance. The results showed that learning by using scaffolded reading method can improve students' reading comprehension on the subjects of Bahasa Indonesian text reading stories of children in SDN 2 Kawalimukti Ciamis District.